Innovative Strategies for Market-Based Disposal of Non-Performing Assets in Small and Medium-Sized Banks - liu, lixia (Pacific International Journal, 2024)
Small and medium-sized banks (SMBs) play a crucial role in the financial system, particularly in supporting regional economies and small enterprises. However, the growing issue of non-performing assets (NPAs) poses significant challenges to their sustainable development. This study explores the market-based disposal mechanisms of NPAs in SMBs, proposing innovative strategies and breakthrough paths. By analyzing industry trends, regulatory changes, and the challenges faced by SMBs, this paper presents actionable recommendations aimed at improving NPA disposal efficiency. Key strategies include asset grouping, strategic partnerships, and leveraging financial technologies such as big data and blockchain. This research provides a practical reference for SMBs in addressing NPA challenges effectively.